REDESIGN BUKU CERITA DINOSAURUS UNTUK ANAK KELAS 4-6 SD DENGAN SISIPAN KOMIK STRIP EDUKATIF - Febby Risyanti Wahyuni; Wildan Hanif; Nia Emilda (Jurusan Seni Rupa ISBI Bandung, 2021)
The books presented for children in Elementary School (SD) have very few pictures, their contents are always filled with words or numbers. This learning process will lead to difficult to learn, especially among children. In this case, especially the function of children's art education is to bringing children's ability to think with visual or visual media. Based on this theory, it can be concluded that there is no need for a contradiction between spoken language and visual language in a learning system because in principle, study activities are an activities that requires both thought and imagination. Prof. Dr. H Primadi Tabrani says that